Haze-Free Highly Transparent Glass Substrates with Nanostructured Surface by Using Self-Assembled Ag Etch Masks. (4th November 2015) - Zhao, Dan; Lee, Illhwan; Park, Jae Yong; Cho, Sang-Hwan; Choi, Chung Sock; Song, Seung-Yong; Kim, Jong Kyu; Lee, Jong-Lam
Abstract : Nano- or micro-structured glass substrates have been widely used for displays, but have a significant drawback called haze that blurs the images. To eliminate haze while maintaining high total optical transmittance ( Ttotal ), the optimized design of textured structures on single- and double-side glass substrates was investigated using a rigorous coupled-wave analysis method. With optimized truncated cone-shaped nanostructures having period ( Λ ) = 200 nm, top-diameter to bottom-diameter ratio ( R ) = 0.4 and height ( h ) ≥ 150 nm on both sides of glass substrates, we achieved a haze-free substrate with an average Ttotal = 99.5% in the wavelength ( λ ) range 300–800 nm.